Age at immigration and the education outcomes of children - Miles Corak (Institute for the Study of Labor (IZA), 2011)
The successful acquisition of a language is often characterized in terms of critical periods. If this is the case it is likely that children who migrate face different challenges in attaining high school credentials depending upon their age at immigration. This paper examines the education outcomes of a cohort of immigrants who arrived in Canada as children. The 2006 Census is used and it is found that there is in fact a distinct change in the chances that children will hold a high-school diploma according to the age at which they arrived in the country. The chances of being a high-school dropout do not vary according to age at arrival up to about the age of nine, with children arriving after that age facing a distinct and growing increase in the chances that they will not graduate from high school. The findings suggest that public policy addressing the long run success of immigrant children needs to be mindful of the variation in risks and opportunities by age, and the role of both early childhood investment and the structure of the education system faced by young adolescents in determining them.
urn:nbn:de:101:1-201111083051
Keywords: I29; J13; 330; children; immigration; education; Kinder; Migranten; Mehrsprachigkeit; Bildungsniveau; Kanada